Stirner: a wanderer of the spirit (Nóema, 2013)
Even before Nietzsche, Stirner opened a crak inside the metaphysical western tradition, that always considered life as something that must be judged, understood and evaluated, and that used knowledge as the instrument to go deep in the truth of being. In The Ego and His Own we attend the attempt to reverse this tradition: thinking does not have the function to conceive and found what is «real», but it does make tough and assure the loss of concerns. The unbelief and the loss of concerns are the elements of Stirner’s spectrology that, instead of imposing the laws of real life, it begins to fight «new battles» against the huge and horrible shadow of God. One of these battles, the one Stirner hard devote himself to, is the «Man’s death».
Keywords: Stirner; Feuerbach; anti-humanism; criticism of the truth